Hospital Surgical Volume, Utilization, Costs and Outcomes of Retroperitoneal Lymph Node Dissection for Testis Cancer - Hua-yin Yu; Nathanael D. Hevelone; Sunil Patel; Stuart R. Lipsitz; Jim C. Hu (Advances in Urology)
Objectives. Retroperitoneal lymph node dissection (RPLND) outcomes for testis cancer originate mostly from single-center series. We characterized population-based utilization, costs, and outcomes and assessed whether higher volume affects outcomes. Methods and Materials. Using the US Nationwide Inpatient Sample from 2001–2008, we identified 993 RPLND and used propensity score methods to assess utilization, costs, and inpatient outcomes based on hospital surgical volume. Results. 51.6% of RPLND were performed at hospitals where there were two or fewer cases per year. RPLND was more commonly performed at large urban teaching hospitals, where men were younger, more likely to be white and earning incomes exceeding the 50th percentile (all P≤.05). Higher hospital volumes were associated with fewer complications and more routine home discharges (all P≤.047). However, higher volume hospitals had more transfusions (P=.004) and incurred $1,435 more in median costs (P<.001). Limitations include inability to adjust for tumor characteristics and absence of outpatient outcomes. Conclusions. Sociodemographic differences exist between high versus low volume RPLND hospitals. Although higher volume hospitals had more transfusions and higher costs, perhaps due to more complex cases, they experienced fewer complications. However, most RPLND are performed at hospitals where there were two or fewer cases per year.